Abordaje del síndrome de hombro doloroso desde la Atención Primaria de Salud: una propuesta esquemática basada en factores clínicos y demográficos - Vacarezza A. , Antonia; Diaz L., Cristobal; Andahur T. , Aaron; Robles G., Guillermo; Debandi C., Anibal (Revista Hospital Clínico Universidad de Chile, 2025)
Painful shoulder syndrome is the third most common reason for consultation due to musculoskeletal disorders in primary health care (PHC). This condition carries significant morbidity and places a considerable burden on higher-level hospitals, mainly due to unnecessary referrals resulting from inadequate initial management. This article proposes a structured framework for managing painful shoulder syndrome from the PHC perspective. It outlines the most prevalent clinical situations and the populations most frequently affected, offering a diagnostic and therapeutic algorithm that incorporates patient demographics, guiding factors toward the most likely pathologies. Once a diagnostic hypothesis has been formulated, and without red flags, initial management should include analgesia and physical therapy. Advanced imaging studies (ultrasound or magnetic resonance) should be reserved for cases where clinical suspicion warrants them. If pain persists for more than three months, depending on the suspected condition, referral to specialties such as orthopedics for further evaluation or physiatry for chronic pain management should be considered.